454-Pyrosequencing Reveals Variable Fungal Diversity Across Farming Systems - Kazeeroni, Elham A.; Al-Sadi, Abdullah M. (Frontiers in Plant Science, 2016)
Oasis farming system is common in some parts of the world, especially in the Arabian Peninsula and several African countries. In Oman, the farming system in the majority of farms follows a semi-oasis farming system, which is characterized by growing multiple crops mainly for home consumption, but also for local market. This study was conducted to investigate fungal diversity using pyrosequencing approach in soils from a farm utilizing a semi-oasis farming system (SOF) which is cultivated with date palms, acid limes and cucumbers. Fungal diversity from this farm was compared to that from an organic farm (OR) growing cucumbers and tomatoes. Fungal diversity was found to be variable among different crops in the same farm. The observed OTUs, Chao1 richness estimates and Shannon diversity values indicated that soils from date palms and acid limes have higher fungal diversity compared to soil from cucumbers (SOF). In addition, they also indicated that the level of fungal diversity is higher in the rhizosphere of cucumbers grown in OR compared to SOF. Ascomycota was the most dominant phylum in most of the samples from the OR and SOF farms. Other dominant phyla are Microsporidia, Chytridiomycota and Basidiomycota. The differential level of fungal diversity within the SOF could be related to the variation in the cultural practices employed for each crop.